Pendidikan Anak Dalam Persfektif Hadis - Hasbi Sidik; Sudirman Sudirman; Muhammad Rusdi Rasyid (Al-Riwayah : Jurnal Kependidikan, 2020)
The focus of this research is to examine children's screening in the hadith. This research method is a qualitative descriptive with a syar'I approach, which examines education in the hadith literature. The results showed that the concept of education in the hadith is a reference to current education. The message of the hadith in educating children is a study that has existed for a long time but has often been ignored. In fact, the current theory of children's education comes from the embryonic guidance in the hadith. However, the explanation of the hadith is still general in nature, only mentions the grid that has been developed by thinkers both in the Islamic world and in the western world